Digital Minority Religions: Introduction - Evolvi, Giulia (2024)
Religion has always been, to a certain extent, mediated. Communication practices are at the core of religious communities, but it is in recent decades that the rapid developments of media technologies have created new possibilities for interactions about religion. In this context, a focus on religious minorities represents a unique opportunity for scholars to analyze the internet in nuanced ways within the framework of digital religion. Through the analysis of minority groups, the internet can be understood both as a space of empowerment of marginal voices and as a venue that further increases social exclusion. In this editorial I outline previous works that show this double-faced role of the internet for minorities, and I offer some reflections on theoretical perspectives for the future of digital minority religions.
Keywords: Hate Speech; Social Media; Internet; Digital Religion; Minorities